P156 Submucosa hypertrophy of active UC patients suggests transmural involvement in UC-associated inflammation. (30th January 2023) - Kucharzik, T; Helwig, U; Strobel, D; Fischer, I; Hammer, L; Rath, S; Maaser, C
Abstract: Background: Transmural response and healing assessed by intestinal ultrasound (IUS) have gained relevance as outcome measures with the ability to guide treatment decisions in inflammatory bowel diseases (IBD). Bowel wall thickness (BWT) is the most widely used IUS parameter and encompasses the thickness of mucosa, muscularis mucosae, and submucosa [1]. Recently, the ratio between submucosa/BWT to estimate endoscopic remission was suggested [2] and de Voogd et al. have shown that the submucosa is the most responsive wall layer [3]. However, little is known about the association between submucosa hypertrophy and clinical as well as lab parameters. Methods: TRUST&UC was a prospective, observational study including 224 UC patients with increased BWT at baseline and active disease (SCCAI ≥ 5) with up to 4 visits (baseline, optional visit at week 2 (W2), W6 and W12). At baseline, patients received therapy intensification according to standard of care. In this post-hoc analysis, 171 patients with a W12 visit ± 4 weeks were included. Overall BWT, mucosa and submucosa thickness were evaluated for the sigmoid colon and stratified for SCCAI, CRP, fecal calprotectin (fCal), and Mayo endoscopic subscore (MES). Results: Active UC patients in our cohort had a median age and disease duration of 37.1 years (28.9 –50.2) and 3.55 years (0.54 – 10.18), more were male (56.6%, n = 95). At baseline, UC patients presented with a high disease activity reflected by a median SCCAI of 9.00 (7.0-10.0). Mean values for BWT, mucosa, and submucosa were 5.54 mm, 1.7 mm, and 2.32 mm, respectively. Over the study course, mucosa and submucosa thickness were significantly reduced with the most pronounced reduction happening within the first 2 weeks (figure 1). Patients with SCCAI ≤ 2 tended to have a more reduced mucosa and submucosa thickness than patients with SCCAI > 2 (fig 2A, A1). Whilst a similar trend was observed for fCal values (not shown), this effect was found neither for CRP (not shown) nor for MES. Conclusion: We found that both mucosa and submucosa thickness of active UC patients were reduced as a consequence of therapy intensification. The lack of difference in thickness of both mucosa and submucosa in patients with and without MES improvement might indicate fibrotic alterations in these patients which needs further evaluation. Based on these and previous results of our group, we suggest measuring BWT in conjunction with other established IUS parameters such as colour Doppler signal to assess disease activity in UC. 1-Ilvermark et al. JCC 2022 2-Miyoshi et al. J Gastroenterol 2022 3-de Voogd et al. Gastroenterol 2022